Application of Teams Games Tournament (TGT) Learning Model To Improve Students Mathematicals Communication Abilities (Eksperimental Research Of Junior High School Students) - Irvan Setyadi Suparman (IKIP Siliwangi, 2020)
The purpose of this article was to determine the improvement of mathematical communication skills between students whose learning using the TGT model was better than traditional learning. The population in this study were students of class VII junior high school on year 2015/2016. Sampling in this study is a simple random sampling and ahe method used in this study is a quasi-experimental study using mathematical communication skills tests. The data processed in this study, namely the gain index is processed using the average two similarity test. Based on the data analysis of the gain index value by the two average similarity test results obtained t count = 0.1382 and t table = 0.1456, with a significance level of 5%. Because t count is outside the -t table to t table intervals, it can be concluded that H0 is rejected, meaning that there is a difference in the increase in mathematical communication skills between students who are learning using the Teams Games Tournament (TGT) model and the traditional model.